Polymorphic perversion of human and other-than-human bodies - Gajewska, Grażyna (Porównania, 2022)
The author examines a range of modes in which the relationship between flora and the human are portrayed. The paper begins with an inquiry into anthropomorphization of plants—a phenomenon firmly established in Western culture—only to show subsequently that such a notional approach has its counterpoise in non-anthropocentric reflection, primarily in post-humanism and new materialism. It is further demonstrated that the studies which emphasize the “vegetal facet of the human” manage to pinpoint both evolutionary and cultural relationships where the human and the non-human are seen to co-exist and cooperate. Then, the author draws attention to the very considerable role that plants play in creating phantasms relating to human gender and sexuality.